CREDIT IN THE ISLAMIC ECONOMIC PERSPECTIVE - Ahmad Wahyu Hidayat; Andi Zamakhsyari Baharuddin; Muhammad Iqbal Fasa (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2018)
In social life, Muslims often encounter forms muamalah. One of the forms muamalah is buying and selling. Sale and purchase allowed by Islam is the buying and selling that does not contain elements of usury, maysir, and gharar. Each transaction is considered valid if it meets the requirements and get along well defined purchase and in accordance to Islamic law. Credit according to Islamic terms is the right to receive payment or obligation to make payment at the time requested, or in the future, because the delivery of the goods now. While the credit sharia financing is known for providing money or bills based on agreements between the company and other parties, which require the other party to restore the funding after a certain period of time in exchange for results.This paper describes about definition, functions, objectives, elements and other types of credit, determine mortgage interest and the goodness and badness of credit, credit in Islamic economic perspective. Islam regards the practice of buying and selling as a legitimate practice and have a great maqasid for sustaining human life, maintain the property, life, lineage, intellect and serenity spiritual and physical. There are also practices in the name of selling but the fact is forbidden usury. The development of the understanding of this practice is consuming a variety of studies, so there is that to allow and forbid. Nothing justifies and forbid the sale and purchase with accounts payable, which is currently known by the term credit.